2015
DOI: 10.1093/heapol/czv028
|View full text |Cite
|
Sign up to set email alerts
|

Towards subsidized malaria rapid diagnostic tests. Lessons learned from programmes to subsidise artemisinin-based combination therapies in the private sector: a review

Abstract: The idea of a private sector subsidy programme of artemisinin-based combination therapies (ACTs) was first proposed in 2004. Since then, several countries around the world have hosted pilot projects or programmes on subsidized ACTs and/or the Affordable Medicines Facility-malaria programme (AMFm). Overall the private sector subsidy programmes of ACTs have been effective in increasing availability of ACTs in the private sector and driving down average prices but struggled to crowd out antimalarial monotherapies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Strengthened policies and regulations may be needed to curtail the availability and distribution of artemisinin monotherapies for malaria case management [28]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strengthened policies and regulations may be needed to curtail the availability and distribution of artemisinin monotherapies for malaria case management [28]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition to supporting interventions targeting provider and consumer behaviour, the policy and regulatory environment may influence the success of copayment mechanisms [ 24 ]. Strengthened policies and regulations may be needed to curtail the availability and distribution of artemisinin monotherapies for malaria case management [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Confirmatory testing has been shown to decrease the inappropriate use of the effective artemisinin-based combination therapy (ACT), which is the first-line treatment for the majority of countries in sub-Saharan Africa (SSA) [ 1 ]. It is thought that reducing inappropriate use of this treatment will impede the rate of resistance to ACT and decrease how much governments will need to spend on purchasing and supplying these medicines to health facilities [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent evaluation of incentives schemes for the use of RDTs by informal private providers in Myanmar compared combinations of price subsidies, financial incentives, and intensified information, education and communication (IEC), and found that a price subsidy combined with intensified IEC resulted in the highest uptake in use and quality of care [ 154 ]. Indeed, several reviews suggest subsidization schemes for RDTs would be wise to learn from the experience of ACT and ensure complementary activities such as community awareness, behaviour change communication (BCC) campaigns and training and supervision of providers are integrated with financial mechanisms [ 137 , 157 ].…”
Section: Resultsmentioning
confidence: 99%